NMR-SPECTRA OF NA- AND RB- IN SOLUTIONS OF SODIUM AND RUBIDIUM IN 1,4,7,10-TETRAOXACYCLODODECANE (12-CROWN-4) - Holton, D; Edwards, P; Johnson, D; Page, C; Mcfarlane, W; Wood, B (1984)
We report the n.m.r. spectra of sodide (Na-) and rubidide (Rb-) ions in the title solvent; these two-component metal solutions represent a convenient, stable source of high concentrations of alkalide ions in solution.